Let's rewrite the given expression correctly:
(2y3 + 3y2 - 4y - 5) / (y + 1)
Dividing the expression between y + 1 we have:
2y2 + y - 5
We can check the result:
(2y2 + y - 5) * (y + 1)
= (2y3 + y2 - 5y + 2y2 + y - 5)
= (2y3 + 3y2 - 4y - 5)
Division OK.
Answer:
The result of the division is:
2y2 + y - 5
4 5/6 - 4 1/2 is 0.33 repeating
If the pieces are cut in the ratio <span>3:5:7</span>, the proportion of each piece to the whole (represented by <span>3+5+7=15</span>) is:
<span><span>3/15</span>:<span>5/15</span>:<span>7/15</span></span>
First, convert the inches to feet also:
1 foot equals to 12 inches.
So 9 inches <span>=<span>9/12</span>×1=0.75</span> feet.
Thus, 33 feet and 9 inches equal <span>33+0.75=33.75</span> feet.
So,
<span>P=<span>3/15</span>×33.75=6.75</span> feet.
<span>Q=<span>5/15</span>×33.75=11.25</span> feet.
<span>R=<span>7/15</span>×33.75=15.75</span> feet.
You can check that these answers are correct by adding up the different pieces: <span>6.75+11.25+15.75=<span>33.75</span></span>
Answer:
a
Step-by-step explanation: